The Enduring Influence of Celestial Bodies in Modern Astrological Practices - Belay Sitotaw Goshu; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
This study looks at how people incorporate astrological practices into their daily lives and investigates the impact of astrology on personal beliefs and decisions. The poll was given to different respondents, indicating degrees of astrological engagement. Books are utilized less frequently than astrology applications, social media, and internet horoscopes by mainstream respondents seeking astrological information. The results show that astrology influences professional selections since it gives many respondents comfort, direction, and influence over relationships. Nonetheless, a significant proportion of the sample indicates that astrology does not influence at all, showing differences in astrology are seen and applied. The study also examines demographic factors like age and educational attainment to understand the broader context of astrological engagement. The conversation offers a thorough examination of astrology's place in modern life by utilizing viewpoints from historical books, online resources, and astrological literature. The findings imply that although astrology offers many people a relevant framework, its impact varies greatly, depending on personal views and the sources of astrological knowledge consulted. This study advances awareness of astrology's continuing influence on social and human dynamics and its persistence in modern spiritual practices.